Organization of the Public Procurement System in Japan and the Possibility of Applying Experience in Russia - I. Yu. Fedorova; Yu. S. Pipiya (Модернизация, инновация, развитие)
Purpose: is to identify the features of the organization of the Japanese public procurement system and the applicability of the positive experience for Russia. For this, it is necessary to study the organization of the public procurement system in Japan, highlighting the most effective elements and tools; to show the features of the functioning of the system and possible ways of future development; to give a comparative description of the procurement systems of Japan and Russia; to suggest ways to improve the Russian procurement system, using the experience of Japan.Methods: during the work, general scientific and special research methods were used, including statistical analysis, processing of analytical data, analogies, scientific generalizations, etc.Results: as a result of the analysis of changes in the legislative framework, on the basis of which public procurement in Japan is regulated, the authors examined the qualitative characteristics of the interconnections of the procurement system participants and assessed the development prospects, incl. Special attention is paid to the content and hierarchy of regulatory legal acts regulating the scope of procurement.The important link of the author's research was the procedure for organizing procurement in the course of applying various types of procurement procedures, including open, selective and limited procurement methods. A comparative analysis of the procurement systems of Japan and the Russian Federation allowed us to determine the similarities and differences in the organization of the procurement process.Conclusions and Relevance: as a result of the analysis the validity of the execution of the state order through the competitive procurement system used in world practice has been substantiated. This formed the basis of the targeted approach and the identification of promising directions in the development of the public procurement system in Japan until 2030. The authors highlight the areas that are successfully implemented in the field of public procurement in the Russian Federation. This indicates the positive development of the Russian system, which was created taking into account the best international experience, including Japanese practice. To improve the mechanism of interaction between participants and exchange of experience in the public procurement system, directions have been identified and the most effective tools have been identified.